Bride of Frankenstein [videorecording (DVD)] - Whale, James, 1889-1957; Karloff, Boris, 1887-1969; Clive, Colin, 1900-1937; Hobson, Valerie, 1917-1998; Lanchester, Elsa, 1902-1986; Thesiger, Ernest, 1879-1961; Frye, Dwight, 1899-1943; Shelley, Mary Wollstonecraft, 1797-1851 (Universal Studios, 1999)
Baron Frankenstein is blackmailed by Dr. Praetorious into reviving his monster and building a mate for it.